Why Can´t Banksy Be a Woman? The Gendering of Graffiti and Street Art Studies - Pinto, Sofia (Street Art & Urban Creativity, 2020)
In this article, the question ‘Why Can´t Banksy Be a Woman’ is a point of departure to approach some of the pressing challenges regarding sex and gender in graffiti and street art studies, in order to contribute on the matter of the presence/absence of women graffiti and street artists in this epistemological field. To this aim, I summon feminist contributions on the invisibility of women in the established art world, namely from art historians Linda Nochlin and Griselda Pollock. I map important contributions on the question of women in graffiti, by referring to graffiti scholars Nancy MacDonald and Jessica Pábon-Cólon. As street art has been considered more gender inclusive in regards to conditions of production, I locate restrictions mainly in terms of reception. Finally, I suggest that the question of women in graffiti and street art studies is larger than sex and gender.